Unraveling the Seismic Signal Anomaly at Mount Rinjani Station: In-Depth Exploration with the Detrended Fluctuation (DFA) Analysis Method in Connection with the 2018 Big Earthquake on Lombok Island, West Nusa Tenggara - Bulkis Kanata; Rosmaliati; Teti Zubaidah; Made Sutha Yadnya; Abdullah Zainuddin; Dwi Ratnasari; Nur Fitratunnisa; Muhammad Fajrin Akbar (Postgraduate, University of Mataram, 2024)
We analyzed the seismic signals of the Mount Rinjani station to identify possible seismic anomalies before a series of major earthquakes on Lombok Island in 2018. We observe anomalies before earthquake events Mw >= 5.90. This research applies the detrended fluctuation analysis (DFA) method to investigate possible earthquake precursors associated with the analyzed earthquake. The results showed a relationship between scaling seismic signals (Î±) that exceeds the threshold of Î± values during the analysis period, and there is a deviation of the root mean square fluctuations in the corresponding scaling that should be rising but constant. The value of Î± with constant root mean square fluctuations occurs one to three days before the preliminary earthquake Mw 6.40 (28/07/2018) UTC and eight to 10 days before the main earthquake Mw 6.90 (05/08/2018). The Mw 6.90 earthquake had the most magnitude and could significantly contribute to the appearance of seismic anomalies.